2020
DOI: 10.1212/wnl.0000000000009844
|View full text |Cite
|
Sign up to set email alerts
|

Initial experiences of US neurologists in practice during the COVID-19 pandemic via survey

Abstract: BackgroundThe current coronavirus disease of 2019 (COVID-19) pandemic has caused widespread disease and death. Rapid increases in patient volumes have exposed weaknesses in healthcare systems and challenged our ability to provide optimal patient care and adequate safety measures to healthcare workers (HCWs).ObjectiveTo test the hypothesis that US neurologists were experiencing significant challenges with lack of personal protective equipment (PPE), rapid changes in practice and varying institutional protocols,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 15 publications
2
30
0
3
Order By: Relevance
“…We recommend delivering messages with compassion locations, settings, or departments; pay cuts or other benefit reductions; lack of information or conflicting information; rapidly changing policies; lack of institutional support; workplace conflict; pivoting to telehealth for patient treatment and using other technologies; working from home; having no childcare or other support; and a wide range of other stressors. 5 The prolonged exposure to this stressful situation can result in psychiatric conditions as well as dysfunctional coping mechanisms, such as problematic substance use. A study of 1257 HCPs in China treating COVID-19 positive patients using validated instruments found that more than 50% had depression, more than 45% had anxiety, more than 34% were experiencing insomnia, and 71.5% reported distress.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We recommend delivering messages with compassion locations, settings, or departments; pay cuts or other benefit reductions; lack of information or conflicting information; rapidly changing policies; lack of institutional support; workplace conflict; pivoting to telehealth for patient treatment and using other technologies; working from home; having no childcare or other support; and a wide range of other stressors. 5 The prolonged exposure to this stressful situation can result in psychiatric conditions as well as dysfunctional coping mechanisms, such as problematic substance use. A study of 1257 HCPs in China treating COVID-19 positive patients using validated instruments found that more than 50% had depression, more than 45% had anxiety, more than 34% were experiencing insomnia, and 71.5% reported distress.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of the group is to provide support, mentorship, and encouragement for members in their professional endeavors and to advocate for more visibility and inclusion, particularly for women. Hence, with the challenges that medical professionals are confronting during the COVID-19 pandemic, the enhanced role of medical professionals in society calls for amplifying voices like those of Greenhalgh 4 and Sharma et al, 5 who advocate for protective equipment for the public and HCPs. Greenhalgh,4 in her comprehensive narrative review, highlights the value of the widespread use of face coverings by the public.…”
Section: The Impact Of Covid-19 On Healthcare Professionalsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 However, in a recent survey of practicing neurologists, only 29% had access to a telehealth platform , and just 17% of practices had access to teleneurology in the outpatient setting. 5 The pandemic has also led to the closure of most outpatient therapy centers, creating further difficulties in patient access to treatments. 6 Despite these challenges, providing telehealth to patients with ALS has previously proven (at least on a smaller scale) to be feasible, provide high satisfaction, and maintain a quality of care similar to that of face-to-face visits.…”
Section: Introductionmentioning
confidence: 99%